2023
DOI: 10.3390/jcm12052036
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signatures in Ductal Carcinoma In Situ (DCIS): A Systematic Review and Meta-Analysis

Abstract: Context: Adjuvant radiotherapy (RT) after breast-conserving surgery (BCS) for ductal carcinoma in situ (DCIS) is debated as benefits are inconstant. Molecular signatures for DCIS have been developed to stratify the risk of local recurrence (LR) and therefore guide the decision of RT. Objective: To evaluate, in women with DCIS treated by BCS, the impact of adjuvant RT on LR according to the molecular signature risk stratification. Methodology: We conducted a systematic review and meta-analysis of five articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…To assess the safety of the omission of RT in the low-risk DCIS, the ROMANCE randomized trial [22] integrated CPFs (age 50 years or older, margins ≥ 2 mm, size ≤ 2.5 cm, nuclear grade 1-2, and no necrosis) with biomolecular Luminal A-like features (positive hormonal receptors, HER2 negative, low . High expectations also come from genomic assays, namely Oncotype DCIS and DCISionRT [13,23,24].…”
Section: Lessons From the Pastmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the safety of the omission of RT in the low-risk DCIS, the ROMANCE randomized trial [22] integrated CPFs (age 50 years or older, margins ≥ 2 mm, size ≤ 2.5 cm, nuclear grade 1-2, and no necrosis) with biomolecular Luminal A-like features (positive hormonal receptors, HER2 negative, low . High expectations also come from genomic assays, namely Oncotype DCIS and DCISionRT [13,23,24].…”
Section: Lessons From the Pastmentioning
confidence: 99%
“…The main ongoing trials dealing with genomic signatures in the DCIS setting are reported in Table 1. High expectations are placed not only on providing more reliable estimates of LR risk but also on predicting the response to RT, thus achieving a tailored approach [24].…”
Section: Decision Support Tools: Biomolecular Prediction Modelsmentioning
confidence: 99%
“…This review illustrated representative oncogenic mutations and aberrant expressions of certain genes that reflect clinical outcomes, therapeutic effects, and malignant biological properties. For HR-positive breast cancer patients in the early stage, MGA including Oncotype Dx, MammaPrint, RecurIndex, breast cancer index (BCI), EndoPredict, and Prosigna Prediction Analysis of Microarray 50 (PAM50) are all helpful candidates for precisely predicting clinical outcomes [9][10][11][12][13][14][15]. For patients with metastatic breast cancer, genetic tests that include specific genetic mutations and biomarkers for immunotherapy also help to identify therapeutic targets and monitor efficacy [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It is a lot of research in the area, most of it not introduced into clinical practice, but some of it will be of value. 8 Genetics, genomics, proteomics, and several other -omics are all being investigated. In order to use this in the future, we need a biopsy, or do we?…”
mentioning
confidence: 99%
“…The second aspect of this is all the “‐omics” from molecular biology, this is not discussed in the article. It is a lot of research in the area, most of it not introduced into clinical practice, but some of it will be of value 8 . Genetics, genomics, proteomics, and several other –omics are all being investigated.…”
mentioning
confidence: 99%